Like a puppet on a string … exploring Headteachers' perceived demise of Local Governing Bodies within an English Multi-Academy Trust. (January 2022) - Vinall, Caroline
Multi-Academy Trusts (MAT) have developed organically in England since 2010. As a result, there appears to be a lack of consistency in the interpretation of delegated responsibilities of Local Governing Bodies (LGB). In a small-scale study of Headteacher (HT) accountability within one English MAT, governance was revealed as a major cause for concern. Accountability links between HT performance management, LGBs, Chief Executive Officer (CEO) and Trust Board were unclear. There was a perception of a lack of upward communication and an increase in local 'rubber-stamping' of MAT strategy. It is argued that, whilst LGBs are used as a form of 'chain of command' to monitor individual schools, their actual purpose may be operational; governed and limited by the Trust Board. LGBs appear to have lost their strategic influence in the conversion from maintained school to academy. I suggest that the term 'Local Governing Body' is potentially erroneous in its nomenclature, as some LGBs merely provide a middle level of 'educational responsibility' – puppets on a string.